Promoting Quality Education through Physics Simulations and Collaborative Modeling-Based Learning: Students’ Computational Thinking Dispositions in High School Physics - Elisabeth Pratidhina Founda Noviani; Firza Farahdiba Daeng; Anthony Wijaya; Herwinarso (Postgraduate, University of Mataram, 2026)
Computational thinking skills are essential in the 21st century; therefore, educational institutions must facilitate students in cultivating computational thinking skills. In addition, computational thinking dispositions are also important for students, as a positive attitude toward computational thinking will help them acquire the skills. This study aims to design and implement a collaborative modeling-based physics learning model supported by simulations to cultivate students' computational thinking dispositions. The learning model was implemented in a senior high school physics classroom during instruction on the work and energy topic. Thirty-four students participated in the study. At the end of the learning process, students’ computational thinking dispositions were assessed using a questionnaire. The results showed that students have overall computational thinking dispositions that are at a good level, particularly in confidence, persistence, and collaboration, while their ability to handle ambiguity reached an acceptable level. Moreover, according to the self-assessment, students had frequently engaged in computational thinking practices during the learning activities. These findings suggest that collaborative modeling-based learning supported by physics simulations has strong potential to promote computational thinking dispositions.